Assessing children's written texts: a framework for equity. (3rd March 2017) - Bearne, Eve
Abstract: In this article, I confine myself to the situation in England that offers a paradigm example of one of the fundamental tensions besetting teaching and assessing writing: the stranglehold of an individualistic view of writing development as opposed to a more socio‐cultural perspective. Examining the uses of summative assessment for accountability purposes and the exclusion of students' multimodal text knowledge and experience, I propose a descriptive framework that can support formative assessment. It encompasses the English national curriculum programmes of study for writing and the associated assessment criteria as well as the features of multimodal texts. Two case studies exemplify using the framework to analyse the writing of students whose accomplishments cannot be fully given value by the current assessment and accountability regime. Finally, I suggest that professional development and respect for professionalism are needed to give teachers the means to reconcile some of the tensions between the urge to teach creatively and imaginatively and their responsibility to their students to cover curricular requirements.